Head Teachers and Teachers as Pioneers in Facilitating Dyslexic Children in Primary Mainstream Schools - Fahima Salman Jaka (Journal of Education and Educational Development, 2020)
This study explores the perceptions of school heads and teachers in facilitating young dyslexic children in primary mainstream schools of Pakistan. Through purposive sampling, the researcher selected eight participants: Four primary school heads and four primary teachers from elite schools of Karachi. The research instrument selected for this study was in-depth interviews to get a deeper insight of school heads and teachers perceptions regarding the facilitation of dyslexic children. The findings revealed that children with dyslexia face many emotional and academic problems and only a few elite schools provide policy to facilitate them in mainstream education. Findings showed that some schools hired remedial teaching services or special education services and the school heads and primary teachers put in immense effort in preparing intervention plans and evaluation plans to suit individual and young dyslexic children needs. It was also suggested that positivity of the learning environment depends upon the teachers. The findings further disclosed that unlike the more developed nations, apart from a few elite schools in Pakistan, there is no importance paid to professional training related to dyslexia.
Keywords: emotional and academic problems; dyslexic children; intervention plans; mainstream schools; remedial teachers